2011
DOI: 10.1111/j.1468-2494.2011.00673.x
|View full text |Cite
|
Sign up to set email alerts
|

In vitro human skin permeation and cutaneous metabolism of catechins from green tea extract and green tea extract-loaded chitosan microparticles

Abstract: Catechins are major antioxidants in green tea (Camellia sinensis or Camellia assamica), but because they do not permeate the skin well, the application of green tea in cosmetic products has so far been limited. This study aims to evaluate the cutaneous absorption of catechins from an extract of green tea and from a green tea extract-loaded chitosan microparticle. The catechin skin metabolism was also examined. The results suggest that chitosan microparticles significantly improve the ability of catechins to pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 57 publications
1
35
0
2
Order By: Relevance
“…This extract presents a high content of phenolic compounds with several pharmacological properties including anti-aging activity. In addition, the cutaneous 4 absorption of green tea extract compounds was studied, both in free and microencapsulated forms (Wisuitiprot et al, 2011). In what concerns the encapsulation of isolated compounds for cosmetic applications, rosmarinic acid (Kim et al, 2010) and quercetin (Sacalia and Mezzena, 2009) were studied using polycaprolactone and lipidic matrices, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…This extract presents a high content of phenolic compounds with several pharmacological properties including anti-aging activity. In addition, the cutaneous 4 absorption of green tea extract compounds was studied, both in free and microencapsulated forms (Wisuitiprot et al, 2011). In what concerns the encapsulation of isolated compounds for cosmetic applications, rosmarinic acid (Kim et al, 2010) and quercetin (Sacalia and Mezzena, 2009) were studied using polycaprolactone and lipidic matrices, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…First, a calibration curve of standard solution containing standard EGCG in ethanol was prepared at concentrations of 7,8,10,15,20, and 24 ppm to give A (absorbance) of 0.2-0.8 at λ max =275 nm [11]. EGCG concentration in the crude extract of green tea was determined using the calibration curve.…”
Section: Methodsmentioning
confidence: 99%
“…Topical EGCG modulates the biochemical pathways involved in the inflammatory response, cell proliferation, and the tumor-promoter response, and is also a marker of skin inflammation induced by mild UV light [8]. EGCG is soluble in water and ethanol [9], but it has low skin-penetrating ability [10]. In this study, to overcome the problem of low permeation of active substances through skin layers and to increase their stability, a topical antioxidant preparation based on niosomes was prepared.…”
Section: Introductionmentioning
confidence: 99%
“…10 With regard to the transdermal systems, there is still a challenge; catechins have low skin permeability due to their hydrophilic nature and chemical interaction with skin lipid bilayers. 11 Several researchers have studied the cutaneous permeation profiles of catechins in topical formulations and they have shown that the main active component (EGCG) has limited penetration through human skin. [12][13][14][15] However, its passage through skin could be improved by incorporating it into transdermal vehicles.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15] However, its passage through skin could be improved by incorporating it into transdermal vehicles. 11 In addition, a transdermal drug could give consumers an alternative delivery mechanism (Scheme 1), wherein the first-pass hepatic metabolism of catechins is avoided. 12,16 Consequently, green tea extract (GTE) can be incorporated into a new formulation.…”
Section: Introductionmentioning
confidence: 99%